Eurêka, eurêka. Archimède et la naissance de la mythologie de la science - Mireille Courrént (Pallas, 2009)
Just as Archimedes’ scientific work is devoid of any resort to mythology, likewise does the image of his genius, as created by the literature of Antiquity, fall within the province of mythology. The Latin writers, as Vitruvius and Livy, were responsible for the depiction of the celebrated moments of the Greek scientist’s life : the episode of the bath, the defense of Syracusi besieged by the Romans and his death at the end of the same siege. But the Latins’ admiration for the practical mind of the Greek scientist was fiercely inveighed against by Plutarch who, in the Life of Marcellus, swung Archimedes’ life into mythology and gave birth not only to the legend of Archimedes (fostered by vastly posterior episodes such as the blazing mirrors and the setting into flame of the Roman vessels), but more generally to the mythology of sciences, which compensates our incomprehension of scientific language by a wondering admiration of the scientist, Galileo, Newton, Einstein…